2006
DOI: 10.1097/01.dad.0000185146.83799.24
|View full text |Cite
|
Sign up to set email alerts
|

Muir-Torre Syndrome With Intriguing Squamous Lesions

Abstract: Muir-Torre syndrome (MTS) is an autosomal, dominantly inherited disorder characterized by sebaceous neoplasms and visceral malignancies. We report a 56-year-old woman who underwent resections of extraocular sebaceous carcinoma, sebaceous epithelioma, actinic keratosis, and keratoacanthoma (KA)-like squamous cell carcinoma (SCC) with venous invasion metachronously over a 9-year period. Because of the mixed, unusual features of the skin lesions, and her history of endometrial and colorectal cancers that had been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…NCCN guidelines show that patients with MLH1 or MSH2 germline mutation have a high cancer predisposition rather than those with MSH6 and PMS2 mutation, not only in the colon and rectum, but also in other organs. Parry et al have reported the risk of metachronous CRC with LS undergoing 9 There is a possibility that the phenotype of CRC might be stronger in Muir-Torre syndrome than in other LS. There is no risk stratification in the same gene mutation group at present, but we must carefully identify high-risk LS patients; for example, those who are detected with colorectal neoplasms during annual SC or who have a strong family history.…”
Section: Discussionmentioning
confidence: 99%
“…NCCN guidelines show that patients with MLH1 or MSH2 germline mutation have a high cancer predisposition rather than those with MSH6 and PMS2 mutation, not only in the colon and rectum, but also in other organs. Parry et al have reported the risk of metachronous CRC with LS undergoing 9 There is a possibility that the phenotype of CRC might be stronger in Muir-Torre syndrome than in other LS. There is no risk stratification in the same gene mutation group at present, but we must carefully identify high-risk LS patients; for example, those who are detected with colorectal neoplasms during annual SC or who have a strong family history.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is well documented that the development of SCCs is linked to ultraviolet light exposure, specifically cumulative lifetime exposure to ultraviolet radiation, other risk factors and clinical syndromes have been clinically demonstrated to contribute to the development of SCC. Ionizing radiation, 5 arsenic, 6 cigarette smoking, 7 human papillomavirus, 8 and organ transplantation 9 are some of the acquired risk factors, whereas xeroderma pigmentosum, 10 oculocutaneous albinism, 11 Ferguson-Smith syndrome, 12 and Muir-Torre syndrome 13 represent examples of predisposing inherited syndromes. SCCs have also been reported to have arisen in chronic, nonhealing wounds and ulcers, 14 burn scars, 15 sites of radiation exposure, 16 and certain inflammatory conditions such as dystrophic epidermolysis bullosa, 17 lupus erythematosus, 18 lichen planus, 19 lichen slcerosis, 20 and porokeratosis.…”
Section: Discussionmentioning
confidence: 99%
“…Nishizawa et al. 3 described a case of MTS characterized by multiple skin lesions (sebaceous carcinoma, sebaceous epithelioma, AK and SCC) associated with visceral malignancies (colorectal and endometrial cancers) and showed loss of MSH‐2 expression in all these skin lesions and also in the visceral malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent visceral neoplasm associated with MTS is colorectal cancer (50%) followed by genitourinary neoplasms (25%) 4 . Other associated tumours include endometrial, breast, lung, gastric, small intestine and haematological malignancies 3,4 . These tumours may appear many years before or after the skin lesions 4 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation